Assessment of trace metals contamination in soil, leaf litter and leaf beetles (Coleoptera, Chrysomelidae) in the vicinity of a metallurgical factory near Menzel Bourguiba (Tunisia). Issue 4 (19th May 2018) - Ghannem, Samir; Touaylia, Samir; Bejaoui, Mustapha
ABSTRACT: Metal pollution is a major environmental danger owing to the rapid increase of urbanization and anthropogenic activities, which may damage the fauna and flora. Insects are often used as bioindicators of the accumulation of toxic elements. We measured concentrations of Cu, Fe, Mn, Zn, Al, and Pb in soil, litter and leaf beetles: Oulema gallaeciana (Heyden, 1879) and Lachnaia paradoxa (Olivier, 1808) at four sampling sites at different distances from metallurgical factory near Menzel Bourguiba (Tunisia). Metal concentrations did not extend beyond a distance of 4 km and were restricted to the immediate surroundings. Significant difference between sites was found for Cu, Fe, Al, and Mn concentrations in leaf litter and only for Pb in soil. In the case of Lachnaia paradoxa, no significant differences were found in the contaminant, except for Cu. The concentrations of Fe and Cu were high in Oulema gallaeciana . Positive correlations were detected for metals in the soil, leaf beetles and leaf litter. Our study confirms that the contaminants can transfer from plants to species.